2021
DOI: 10.1371/journal.pone.0249710
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Abbott BinaxNOW rapid antigen test for SARS-CoV-2 infection in children: Implications for screening in a school setting

Abstract: Background Rapid antigen tests hold much promise for use in the school environment. However, the performance of these tests in non-clinical settings and among one of the main target populations in schools—asymptomatic children—is unclear. To address this gap, we examined the positive and negative concordance between the BinaxNOW™ rapid SARS-CoV-2 antigen assay and an RT-PCR test among children at a community-based Covid-19 testing site. Methods We conducted rapid antigen (BinaxNOW™) and oral fluid RT-PCR (Cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
56
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(64 citation statements)
references
References 10 publications
7
56
1
Order By: Relevance
“…This finding is in agreement with other published studies 14,15,[32][33][34] . Sood et al recently described that the positive concordance of RADT was higher among symptomatic children (64.4%) compared to asymptomatic children (51.1%) presenting at a walk-in testing site in Los Angeles County 33 . Similarly, L'Huillier et al described a sensitivity of 73.0% in symptomatic vs. 43.3% in asymptomatic children 34 .…”
Section: (Which Was Not Certified By Peer Review)supporting
confidence: 94%
“…This finding is in agreement with other published studies 14,15,[32][33][34] . Sood et al recently described that the positive concordance of RADT was higher among symptomatic children (64.4%) compared to asymptomatic children (51.1%) presenting at a walk-in testing site in Los Angeles County 33 . Similarly, L'Huillier et al described a sensitivity of 73.0% in symptomatic vs. 43.3% in asymptomatic children 34 .…”
Section: (Which Was Not Certified By Peer Review)supporting
confidence: 94%
“…Across other studies, BinaxNOW sensitivity varied between 64.4% to 96.5% among symptomatic persons [6,8,[10][11][12][13] and between 20.0% to 70.2% among asymptomatic participants ( [9,14]). Several factors may contribute to variability in test performance including differences in population characteristics, the timing during disease course, test operator training [7] and methodological differences such as the comparator rRT-PCR assay, specimen type and collection method.…”
Section: Discussionmentioning
confidence: 89%
“…Prior studies [6][7][8][9][10][11][12][13][14] have examined BinaxNOW antigen test performance; however, detailed data on the association of antigen test performance compared to rRT-PCR and viral culture by key epidemiologic characteristics such as symptom and known exposure status, timing during infection, and demographic variables are limited. An earlier brief report [15] analyzing these data showed high specificity for BinaxNOW, but low sensitivity in specimens from either symptomatic (64.2%) or asymptomatic persons (35.8%) and showed improved sensitivity compared to rRT-PCR when limiting the analysis to culture positive specimens.…”
Section: Introductionmentioning
confidence: 99%
“…Searches of PubMed, Google Scholar, medRxiv, and bio-Rxiv yielded 15 unique studies after de-duplication. [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] Studies identified can be found in Appendix 2. Fourteen of the studies examined the BinaxNOW platform, and 1 examined the Cue COVID-19 Test.…”
Section: Resultsmentioning
confidence: 99%